2014
DOI: 10.1260/1747-9541.9.6.1311
|View full text |Cite
|
Sign up to set email alerts
|

The Coaching Behavior Scale for Sport: Factor Structure Examination for Singaporean Youth Athletes

Abstract: The Coaching Behavior Scale for Sport (CBS-S) is designed to evaluate coaches' involvement in developing athletes, taking into considerations the complex training and competition environment. Although the CBS-S has been used in a number of empirical studies, the factor structure of the instrument has not been examined rigorously. The present study was, therefore, conducted to assess the factor structure of the CBS-S for Singaporean youth athletes. A total of 519 participants completed the CBS-S, and their resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
2
9
0
2
Order By: Relevance
“…Koh and colleagues decided, however, to remove one item of the CBS‐S competition strategies subscale, which was argued to be irrelevant for the specific sample under study. Their findings supported the factorial validity of the 46 remaining items, and also the concurrent validity of the CBS‐S with coaching satisfaction (Koh et al., in press).…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Koh and colleagues decided, however, to remove one item of the CBS‐S competition strategies subscale, which was argued to be irrelevant for the specific sample under study. Their findings supported the factorial validity of the 46 remaining items, and also the concurrent validity of the CBS‐S with coaching satisfaction (Koh et al., in press).…”
mentioning
confidence: 53%
“…Moreover, a subscale labeled competition strategies, not included in the initial study (Côté et al., ), was later added (Baker et al., ). To date, only one study has used confirmatory factor analysis (CFA) to confirm the proposed factor structure of the 47‐item version of the scale (Koh et al., in press). Koh and colleagues decided, however, to remove one item of the CBS‐S competition strategies subscale, which was argued to be irrelevant for the specific sample under study.…”
mentioning
confidence: 99%
“…However, they stated that the amount of variance explained was between 55 and 58% for three pairs of variables (goal setting-mental preparation, competition strategies-mental preparation and competition strategies-technical skills). Koh et al (2014) stated that the lowest average scores came from negative personal rapport factor, while the highest average scores came from technical skills factor.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind this finding was considered to rest in the age of athletes and their need for more pre-teaching in comparison with more experienced athletes [26]. In addition to CBS-S validity and reliability research in different nations and various sport types; in Turkish context [12], among athletes from 15 different sports [33], coach-athlete relationship in different sports were examined qualitatively [35], Singaporean youth athletes [36], Swedish athletes [37], volleyball players [38] and Indian athletes [39]. Baker et al [34] examined individual and team sport members.…”
Section: Discussionmentioning
confidence: 99%
“…Coaching behavior research has been widely examined with various ages, levels, and contexts [31,32], supporting the important and pertinent aspects of coaching. The Coaching Behavior Scale (CBS), after extensive review, has been found to be a reliable and valid instrument in the literature; among athletes from 15 different sports [33], team and individual sports [34], coach-athlete relationship in different sports were examined qualitatively [35], Singaporean youth athletes [36], Swedish athletes [37], volleyball players [38] and Indian athletes [39]. The CBS demonstrated that each category is crucial and valuable when evaluating a coach's behavior.…”
Section: Introductionmentioning
confidence: 99%